Unique structural features of flaviviruses’ capsid proteins: new insights on structure-function relationship - Neves-Martins, Thais C.; Mebus-Antunes, Nathane C.; Caruso, Icaro P. [UNESP]; Almeida, Fabio C.L.; Da Poian, Andrea T. (Elsevier, 2021)
The Flaviviridae family comprises important human pathogens, including Dengue, Zika, West Nile, Yellow Fever and Japanese Encephalitis viruses. The viral genome, a positive-sense single-stranded RNA, is packaged by a single protein, the capsid protein, which is a small and highly basic protein that form intertwined homodimers in solution. Atomic-resolution structures of four flaviviruses capsid proteins were solved either in solution by nuclear magnetic resonance spectroscopy, or after protein crystallization by X-ray diffraction. Analyses of these structures revealed very particular properties, namely (i) the predominance of quaternary contacts maintaining the structure; (ii) a highly electropositive surface throughout the protein; and (iii) a flexible helix (α1). The goal of this review is to discuss the role of these features in protein structure-function relationship.